พฤฒพลัง: กรณีศึกษาผู้สูงอายุที่ออกกำลังกายในน้ำ - กิตติพงษ์ รักไทย (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research, with the case study method, is aimed at scrutinizing the process of active ageing development of elderly people attending the aquatic exercise. Gathering data by employing in-depth interviews with four elderly people frequently participating in an aquatic exercise, the researcher found many findings. The first and the second informants, a spouse, expressed that their affection and deep bond between each other made their caretaking for each other meaningful and that such affection and deep bond gave them the power to live. They attended the aquatic exercises regularly and focused on taking care of each other’s many facets of health. Moreover, both of them placed importance on the knowledge sharing society in places for exercise. The third informant, an elderly daughter taking care of her more elderly mother, expressed the fact that her mother still lived under the same roof as hers made her life meaningful and gave her the power to take care of her own health. In addition, her liveliness created more meaningfulness to the aquatic exercise society. The fourth informant went through a health crisis and realized that to always keep her own health fit was the most important thing so that she could remain fully self-dependent. As she was the reliable leader of the aquatic exercise community, her exercise participation did not only simply mean a personal matter, but also valuable mean of relationship. Besides, the four informants had their own economic stability supporting their health caretaking. All of these informants’ attributes are consistent with the active ageing framework as follows: (1) keeping the health fit by exercisingregularly, (2) having economic stability which supports physical activity participation and (3) taking part in exercise community with other elderly people. Thus, the processes leading to the active ageing are the theories of the meaning of life, Erikson's theory of psychosocial development and the activity theory.